Fermentation of Pineapple Taste Juice for the Production of Citric Acid Using Candida Lipolytica ATCC 8661 - Koshy, Joyce (1990)
Fermentation of pineapple waste juice.using Candida lipolytica ATCC 8661 for production of citric acid was conducted. A comparison study was also carried out using the pineapple flesh juice (edible portion). Maximum production of citric acid obtained from the flesh juice and waste juice was 2.5 g/l and 3.2 g/l respectively after 4 Days under submerged fermentation using shake flasks at 30°C .The addition of 0.1% potassium dihydrogen phosphate in the 10Z pure glucose media increased the production of total acids (citric acid). Addition of 3% methanol prior to incubation into the pineapple waste juice showed a remarkable increase in citric acid production. Fermentation of pineapple waste juice using Candida lipolytica ATCC 8661 was also conducted in LH fermentor (Model 500). The effect of different levels of dissolved oxygen saturation (10%, 20%, 30% and 40%) with and without 3% methanol on citric acid production of pineapple waste juice was studied over a 10-day fermentation period at 30C. The maximum citric acid production was 8.2 g/l in sample with 3% methanol having 40% dissolved oxygen saturation after 8 days of fermentation. Maximum of biomass production of 12. 37 mg/ml juice (dry cell weight) was obtained from fermented pineapple waste juice inoculated with C. lipolytica ATCC 8661 having 30% dissolved oxygen saturation after 8-10 days of fermentation.